2004
DOI: 10.1299/jsmea.47.561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Treatment on Interfacial Strength between Bamboo Fiber and PP Resin

Abstract: The interfacial shear strength (IFSS) between a bamboo fiber bundle and maleic anhydride polypropylene (MAPP) was examined for various kinds of surface treatments in conjunction with ultrasonic washing. Bamboo fiber bundles were extracted from Chinese bamboo by either mechanical scratching or steam explosion. The effect of fiber bundle diameter on IFSS was measured by using the micro-droplet test. The test results showed that higher IFSS was observed for bundles having smaller diameter. Isocyanate silane treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 5 publications
0
25
1
Order By: Relevance
“…In comparison to non‐treated composite, the composites with 2 wt% silane coupling agent may increase both tensile strength and tensile modulus as high as 30% and 27%, respectively. This is contrary to other studies where silane coupling agent has a slight effect on the mechanical properties .…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In comparison to non‐treated composite, the composites with 2 wt% silane coupling agent may increase both tensile strength and tensile modulus as high as 30% and 27%, respectively. This is contrary to other studies where silane coupling agent has a slight effect on the mechanical properties .…”
Section: Resultscontrasting
confidence: 99%
“…Most researchers have reported a similar increase in tensile properties with increasing silane coupling agent [10,31]. Adding silane coupling agent has improved fibers dispersal in polymer matrix surface, improvement in adhesion between OCC fibers and polymer matrix and consequently more restriction in polymer chain movement [24]. Proper adhesion between fibers and polymer can promote stress transfer from the matrix to cellulose fibers and result in significant increase in mechanical properties of the samples prepared by coupling agent [32].…”
Section: Tensile Propertiesmentioning
confidence: 98%
“…Chen et al used cardanol as grafting agent in preparation for better performance of composite. In their experiment isocyanate silane and amino silane were used to modify the surface of bamboo fiber [15,16]. In present research mimosa was used for grafting the surface of bamboo fiber.…”
Section: Introductionmentioning
confidence: 95%
“…Li worked on Phyllostachys pubescens bamboo and found 5.14% hot water solubility, 22.11% lignin, 70.84% holocellulose, 47.30% α-cellulose, 1.94% ash [26]. Ghoshal et al worked on bamboo fiber and found 60% cellulose and 32% lignin [16]. During present chemical analysis, alpha cellulose was found to be 50.23±.18% indicating that homopolysacsride consist of β-D-glucopyranose linked together by β,1-4-linkage.…”
Section: Chemical Analysismentioning
confidence: 99%
“…Greenhouse effect has been becoming one of the most serious environmental concerns (Tung and Yamamoto 2004). Polymer composites based on fossil oil cause a heavy burden from the viewpoint of sustained development.…”
Section: Introductionmentioning
confidence: 99%